Diversifikasi Produk Olahan Pisang: Pembuatan Tepung Pisang dan Produk Olahannya Bagi Persekutuan Wanita Jemaat GKI EL Elyon Kotaraja, Jayapura - Keiluhu, Henderina J.; Ngamelubun, Gerardinalia; Warikar, Evie L.; Ramandey, Euniche RPF.; Purnamasari, Vita; Soakakone, Hanna; Nilan, Tarsisiyanti J.A. (Jurusan Biologi FMIPA Universitas Cenderawasih, 2025)
Banana is a tropical fruit plant that is widely known and utilized almost all parts of the plant. Banana fruit can be directly consumed as fresh fruit or processed into fried bananas or banana chips, but very rarely made into banana flour, especially in Jayapura. The purpose of this community service activity is to disseminate the benefits of banana flour as well as training in making banana flour and processed banana flour, so that it can become an entrepreneurial opportunity in addition to self-consumption. The material about banana flour was delivered using the lecture method followed by the practice of making banana flour and making three types of cakes from banana flour. This activity was carried out on August 26, 2023 and September 2, 2023 with 23 participants from the Women's Association of the El Elyon Indonesian Christian Church in Kotaraja, Jayapura. Banana flour is made using the direct drying method under sunlight. Banana flour-based baking products made in this activity are cookies, brownies, and cakes. This activity received a good response and high satisfaction from the participants of 97%.